Phenotypes of children with 20q13.3 microdeletion affecting KCNQ2 and CHRNA4. Issue 2 (June 2015) - Okumura, Akihisa; Ishii, Atsushi; Shimojima, Keiko; Kurahashi, Hirokazu; Yoshitomi, Shinsaku; Imai, Katsumi; Imamura, Mari; Seki, Yuko; Shimizu, Toshiaki; Hirose, Shinichi; Yamamoto, Toshiyuki
Abstract In order to clarify the phenotypes of 20q13.33 microdeletion, clinical manifestations and genetic findings from four patients are discussed in relation to chromosomal microdeletions at 20q13.33. All patients had epileptic seizures mostly beginning within the neonatal period and disappearing by 4 months of age, similar to epilepsy phenotypes of benign familial neonatal seizures. We performed array comparative genomic hybridization analysis in order to investigate the chromosomal aberration. Developmental outcome was good in two patients with deletion restricted to three genes (CHRNA4, KCNQ2, and COL20A1), whereas delay in developmental milestones was observed in the other two with a wider range of deletion. Information obtained from array comparative genomic hybridization may be useful to predict seizure and developmental outcome, however, there is no distinctive pattern of abnormalities that would arouse clinical suspicion of a 20q13.33 microdeletion. Deletion of KCNQ2 and CHRNA4 does not appear to affect seizure phenotype. Molecular cytogenetic techniques, such as array comparative genomic hybridization, will be necessary to clarify the relationship between phenotypes and individual genes within this region.